Gradual wiring of olfactory input to amygdala feedback circuits - Oboti, Livio (Sci Rep, 2020)
The amygdala facilitates odor driven behavioral responses by enhancing the saliency of olfactory signals. Before this processing, olfactory input is refined through the feedback provided by amygdala corticofugal projection (ACPs). Although the saliency of odor signals is subject to developmental changes, the stage at which this cortical feedback first occurs is not known. Using optogenetically-assisted intracellular recordings of the mouse cortical amygdala, we identified changes in the electrophysiological properties of ACPs at different developmental stages. These were consistent with a decrease in neuronal excitability and an increase in the amount of incoming accessory olfactory bulb (AOB) inputs, as confirmed by estimates of release probability, quantal size and contact number at the AOB-to-ACP synapse. Moreover, the proportion of ACPs activated in response to odors was dependent on the stage of development as revealed by c-Fos expression analysis. These results update standard accounts of how the amygdala processes social signals by emphasizing the occurrence of critical periods in the development of its sensory gating functions.